Government Policy in Village Fund Allocation Management As Poverty Alleviation Efforts in Gorontalo .Regency: Government Policy, Village Fund, Poverty - Hendra Hemeto; Arifin Tahir; Titin Dunggio (Journal of Economic, Business, and Administration (JEBA), 2022)
ABSTRACT Reading is one of many ways to acquire information, where people can find it from television and internet. As reading dominates all activities in the English subject, the language. The research method used in this research is qualitative research. In qualitative research there are various kinds of research, and this research is included in case study research, namely making detailed observations of the objects that have been raised in the formulation of the problem and are expected to solve the problems that occur.The results of the study show that 1) the application of the hamlet budget management policy in Batudaa sub-district has been running well. With the hamlet budget implemented by Batudaa Sub-district, it has been implemented well by the Regency Authority, inspectorate, sub-district, Head of PMD, as well as residents including evaluating the results of the application of the sports profession, assessing the deed of responsibility for air, assessing the implementation of community empowerment activities; 2) The encouragement aspect in the hamlet budget management policy in Batudaa District, Gorontalo Regency, as follows: communication, human resources, in the hamlet budget management policy has been implemented well. communication is carried out starting from the hamlet regime level, sub-district level to district level. The communication is carried out in the form of coordination meetings and assessment meetings. Executive records or actions, the bureaucracy has been carried out well.